Combination of sweet orange, lentisk and lemon eucalyptus essential oils: Optimization of a new complete antimicrobial formulation using a mixture design methodology - Al-Mijalli, Samiah Hamad; Jeddi, Mohamed; El Hachlafi, Naoufal; Abdallah, Emad M; Assaggaf, Hamza; Qasem, Ahmed; Rajab, Bodour S; Lee, Learn-Han *; Bouyahya, Abdelhakim; Goh, Khang Wen; Long, Chiau Ming *; Mrabti, Hanae Naceiri (Elsevier, 2023)
Sweet orange (Citrus × sinensis (L.) Osbeck), lentisk (Pistacia lentiscus L.) and lemon eucalyptus (Eucalyptus citriodora Hook) are medicinal plants known by its culinary virtues. Their volatile oils have demonstrated promising antimicrobial activity against a panel of microbial strains, including those implicated in food deterioration. In this exploratory investigation, we aimed to determine the antimicrobial formulation of sweet orange, lentisk and lemon eucalyptus essential oils (EOs) using the simplex-centroid mixture design approach coupled with a broth microdilution method. EOs were first extracted by hydrodistillation, and then their phytochemical profile was characterized using Gas chromatography-mass spectrometry (GC-MS). GC-MS analysis identified d-limonene (14.27%), careen-3 (14.11%), β-myrcene (12.53%) as main components of lentisk EOs, while lemon eucalyptus was dominated by citronellal (39.40%), β-citronellol (16.39%) and 1,8-cineole (9.22%). For sweet orange EOs, d-limonene (87.22%) was the principal compound. The three EOs exhibited promising antimicrobial potential against various microorganisms. Lemon eucalyptus and sweet orange EO showed high activity against most tested microorganisms, while lentisk EO exerted important effect against some microbes but only moderate activity against others. The optimization formulations of antimicrobial potential showed interesting synergistic effects between three EOs. The best combinations predicted on C. albicans, S. aureus, E. coli, S. enterica and B. cereus correspond to 44%/55%/0%, 54%/16%/28%, 43%/22%/33%, 45%/17%/36% and 36%/30%/32% of Citrus sinensis, Pistacia lentiscus and Eucalyptus citriodora EOs, respectively. These findings suggest that the combination of EOs could be used as natural food preservatives and antimicrobial agents. However, further studies are needed to determine the mechanisms of action and efficacy of these EOs against different microorganisms.